Effectiveness of home-based rehabilitation using active video games on quality of life, cognitive and motor functions in people with Parkinson's disease: a systematic review. Issue 26 (18th December 2022) - Gallou-Guyot, M.; Nuic, D.; Mandigout, S.; Compagnat, M.; Welter, M. L; Daviet, J. C; Perrochon, A.
Abstract: Purpose: We summarized the effectiveness of home-based active video game interventions on physical and cognitive functions, as well as quality of life in adults with Parkinson's disease. We also assessed the feasibility, safety, adherence, and retention of benefits of these interventions. Method: We searched studies in eight databases from 1st March to 30th November 2020. Two authors independently performed the selection, data extraction and risk of bias evaluation (PROSPERO ID: CRD42020178138). Results: Nine studies were included in this systematic review (412 participants). All in all, home-based active video games were found effective in improving gait and balance functions in people with Parkinson's disease, equivalent to usual care and conventional therapy. No conclusion can be drawn on cognition and quality of life. Home-based active video games seemed feasible, safe, and were enjoyed by people with Parkinson's disease. The optimal dose, the need for supervision and the retention of benefits of these interventions are still to be determined. These results should be interpreted carefully, considering the limited number of included studies and their small sample sizes, the widespread heterogeneity of included studies and their medium average methodological quality. Conclusion: Future research should focus on the effects of home-based active video games on impairments specific to Parkinson's disease, such as falls, freezing of gait and attention, as well as the dose, need for supervision and retention of the benefits of these interventions. IMPLICATIONS FOR REHABILITATION: Home-based active video games are effective in improving motor functions in people with PD. No conclusion can be drawn regarding cognition in people with PD. No conclusion can be drawn regarding quality of life in people with PD. Home-based active video games seem feasible and safe, and are enjoyed by people with PD. The dose, need for control and retention of the benefits still need to be determined.